Improve feature selection method of web page language identification using fuzzy ARTMAP. (16th November 2010) - Ng, Choon-Ching; Selamat, Ali
The information available in languages other than English on the World Wide Web and global information systems is increasing significantly. Different languages can be produced by using one particular script such as Arabic, Persian, Urdu and Pashto that use Arabic script letters. The issue is how to produce reliable features of a web page that is to undergo language identification. Incorrectly identifying the language results in garbled translations as well as faulty and incomplete analyses. The aim of this study is to enhance the effectiveness of feature selection method of web page language identification. We have investigated total N-grams, N-grams frequency, N-grams frequency document frequency, and N-grams frequency inverse document frequency of web page language identification. From the experimental results, it is proven that N-grams frequency gives the most promising result compared to other feature selection methods.